Novel Approach for Dealing with Partial Differential Equations with Mixed Derivatives - Abdon Atangana; Suares Clovis Oukouomi Noutchie (Abstract and Applied Analysis)
We propose a powerful iteration scheme for solving analytically a class of partial equations with mixed derivatives. Our approach is based upon the Lagrange multiplier in two-dimensional spaces. The local convergence and uniqueness of the proposed method are analyzed. In order to demonstrate the applicability of our method, we present an algorithm to compute the solution for two examples.